Smart EV Charging Station with Automated Payment System - Gangarde Bhagyashri; Khedkar Dipti; Mhaske Nikita; Prof. Shelke Satish; Dr. Sudhir Divekar (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The growing adoption of electric vehicles (EVs) necessitates advancements in charging infrastructure to enhance convenience and effeciency. This project focuses on developing a wireless EV charging system integrated with a real-time payment gateway, eliminating the need for physical cables. The system utilizes electromagnetic induction to transfer power wirelessly from a charging pad installed in parking areas to a receiver in the vehicle. This method enhances user convenience by allowing automatic charging when vehicles park in designated spots, reducing reliance on plug-in chargers. The payment system ensures seamless authentication, real-time billing, and transaction security, making EV charging hassle-free and effecient.